Development of a service based mobile application for android phones - Soon, Xin Rong (2018)
The advancement of technology in the world today has helped to change people's lives even more so as the world continues to strive towards a digital lifestyle. Everything that used to be offline has been moved online with the help of technology. An example of that would be the usage of service based mobile applications. In the current market, there are already several service-based mobile applications that have helped to serve the service industry in a more efficient way. However, such applications only focus on providing services on a professional level, missing out on the untapped platform of students. Students, even though they are still in school and would not have much professional work experience, they are still able to contribute their expertise in the service industry. However, in those service-based mobile applications, they are unable to compete against experienced adults. As an inspiration, I would focus on creating a mobile application based social platform that will be able to provide an opportunity for students to serve the service industry as a service provider. This untapped potential would be beneficial to both the students as service providers as well as service receivers. Students are able to earn extra allowance while imparting their knowledge – be it in the form of academic tuition or music lessons. Furthermore, by encouraging students to work while studying would arguably prepare them for the working society earlier and train them to be more independent. Service providers, on the other hand, would be able to learn from these students are a considerably lower rate compared to professionals. Such service application would also attract youngsters in Singapore to maybe pick up a new skill. After researching on the mobile application technologies available and the demands of the current market industries, hybrid application technology was chosen as the main development platform for this mobile application as it is faster and easier to maintain compared to the native application. This developed mobile application named “I service provider” can be run on both Android and iOS, in addition to a website that users can use without any incurring additional costs, allowing for a wider scale of potential users.